Mature landfill leachate treatment by denitrification and ozonation - Cortez, Susana (2011)
The removal of nitrate from a mature landfill leachate with high nitrate load in a lab-scale anoxic rotating biological contactor (RBC) was studied. Under a phosphorus-phosphate concentration of 10mg P-PO4 3− L−1 and nitrogen-nitrate concentrations above 530mgN-NO3 − L−1 the reactor achieved nitrogennitrate removal efficiencies close to 100%, without nitrite or nitrous oxide accumulation. Although the reactor presented a very good denitrification performance, the effluent carbon concentration was still above the legal discharge value. In order to increase the biodegradability of the leachate recalcitrant carbon load, a pre-ozonation was further investigated. The pre-ozonation led to a total organic carbon (TOC) removal of 28%. The sequence of treatments, leachate ozonation followed by RBC denitrification did not affect the denitrification efficiency. In fact, it was possible to attain a denitrification rate of 123mg N-NO3 − L−1 h−1. The moderate decrease in the carbon load of the final effluent indicated that some recalcitrant compounds were still present after ozonation. The anoxic RBC showed to be a promising technology for removing nitrate from landfill leachate.